Development of the Malaise trap: how to streamline the search for micro insects - Partanen, Saku (My University, 2022)
Insects are the most diverse group of animals on planet Earth, but our knowledge of them on a species level is quite limited. Entomologists have many tools in their arsenal to try to diminish the gap between knowledge and ignorance. One tool in particular is used to survey flying insects in large quantities in an area of interest. The Malaise trap designed by Réne Malaise is a tent like structure that passively collects insect samples and stores them inside a collector bottle for later inspection. The inspection process is laborious in any case, but if an entomologist is interested in the world of microscopic insects, the task is even more arduous. This thesis aimed to design a tool to ease the search for the smallest insects by combining the power of a Malaise trap with a passively sorting collector and to answer the question whether or not a malaise trap collector can be developed to sort insects? The tool was tested in the field in Turku, Finland, for a period in the summer of 2020 and the samples were stored in groups that represent the part of the collector they had been sorted to. Later, each individual insect’s fore wing was measured. Insect were set in a class by the size of their fore wing and the probability of each member of a class to end up in the bottom part of the collector was calculated. Also, a comparative time trial study between the new sorting collector and a standard collector was performed to see if a temporal difference in insect hand sorting can be found. After analyzing the data, it was found that 92% of insects with fore wings smaller than 1 mm were sorted in a desired fashion and that there was no difference in the times elapsed during the time trial test. It was concluded that the tool works, but it should be used only after considering the possible pros and cons.

Hyönteiset ovat maapallon monipuolisin eläinryhmä, mutta meidän lajitason ymmärryksemme niistä on edelleen hyvin rajallinen. Hyönteistutkijoilla on käytössään monipuolinen arsenaali työkaluja, joilla tiedon ja tietämättömyyden välistä kuilua koitetaan kuroa pienemmäksi. Yhtä näistä käytetään erityisesti lentävien hyönteisten tutkimiseen suurella näyte määrässä. Malaise-pyydys on Réne Malaisen kehittämä telttamainen rakennelma, joka kerää passiivisesti hyönteisnäytteitä keräyspulloon ja säilöö niitä myöhempää tarkastusta varten. Tarkastus on työlästä kaikissa mittasuhteissa, mutta erityisen vaivalloista silloin, kun hyönteistutkija haluaa perehtyä mikroskooppisten hyönteisten maailmaan. Tämä opinnäytetyö pyrki kehittämään työkalun, joka yhdistettynä Malaise-pyydyksen tehokkuuteen, helpottaa pienimpien hyönteisten löytämistä ja vastaa kysymykseen: voiko keräyspulloa kehittää hyönteisiä passiivisesti lajittelevaksi? Työkalua testattiin Suomen Turussa tiettynä kesän aikana. Hyönteisnäytteet talletettiin erillisiin ryhmiin niiden keräyspullon eri osista löytymisen mukaan ja myöhemmin jokaisen hyönteisen etusiiven pituus mitattiin. Hyönteiset asetettiin luokkiin niiden siipien pituuden mukaan ja todennäköisyys sille, että luokan jäsen päätyisi pullon alaosaan laskettiin. Uuden lajittelevan keräyspullon ja vanhan pullon välillä testattiin, löytyykö hyönteisten käsilajittelussa ajallista eroa. Datan analyysien jälkeen huomattiin, että 92 % hyönteisistä, joilla etusiivenpituus oli alle 1 mm, päätyi toivotulla tavalla keräyspullon alaosaan, ja että käsinlajitteluiden välillä ei ollut tilastollisesti merkitsevää ajallista eroa. Todettiin, että työkalu toimii, mutta sen käyttöönotossa tulee huomioida kaikki sen hyödyt ja haitat.
Keywords: Malaise trap, Collector bottle, Micro insects, passive sorting